A unique dual acyltransferase system shared in the polyketide chain initiation of kidamycinone and rubiflavinone biosynthesis - Kyung Taek Heo; Byeongsan Lee; Byeongsan Lee; Gwi Ja Hwang; Beomcheol Park; Beomcheol Park; Jun-Pil Jang; Bang Yeon Hwang; Jae-Hyuk Jang; Young-Soo Hong (Frontiers in Microbiology, 2023)
The pluramycin family of natural products has diverse substituents at the C2 position, which are closely related to their biological activity. Therefore, it is important to understand the biosynthesis of C2 substituents. In this study, we describe the biosynthesis of C2 moieties in Streptomyces sp. W2061, which produces kidamycin and rubiflavinone C-1, containing anthrapyran aglycones. Sequence analysis of the loading module (Kid13) of the PKS responsible for the synthesis of these anthrapyran aglycones is useful for confirming the incorporation of atypical primer units into the corresponding products. Kid13 is a ketosynthase-like decarboxylase (KSQ)-type loading module with unusual dual acyltransferase (AT) domains (AT1-1 and AT1-2). The AT1-2 domain primarily loads ethylmalonyl-CoA and malonyl-CoA for rubiflavinone and kidamycinone and rubiflavinone, respectively; however, the AT1-1 domain contributed to the functioning of the AT1-2 domain to efficiently load ethylmalonyl-CoA for rubiflavinone. We found that the dual AT system was involved in the production of kidamycinone, an aglycone of kidamycin, and rubiflavinone C-1 by other shared biosynthetic genes in Streptomyces sp. W2061. This study broadens our understanding of the incorporation of atypical primer units into polyketide products.